Alimentación Saludable: Crucigrama sobre meriendas nutritivas - Emily Minton (EDIS)
Learn about smart snacking with this simple crossword puzzle activity. This 1-page fact sheet was written by Emily Minton and published by the UF Department of Family Youth and Community Sciences, May 2011.